Identifying vulnerable mother-infant dyads: a psychometric evaluation of two observational coding systems using varying interaction periods - Sharp, Helen; Vitoratou, Silia; O’Mahen, Heather; Bozicevic, Laura; Refberg, Miriam; Hayes, Chloe; Gay, Jessica; Pickles, Andrew (Frontiers in Psychology, 2024)
Introduction: Clinical services require feasible assessments of parent-infant interaction in order to identify dyads requiring parenting intervention. We assessed the reliability and predictive validity of two observational tools and tested whether briefer forms could be identified which retain acceptable psychometric properties over short observation periods. Methods: A stratified high-risk community sample of 250 mother-infant dyads from The Wirral Child Health and Development Study completed 7-minute play-based interaction at 6-8 months. Film-footage was independently coded by two trained raters using PIIOS and NICHD-SECCYD systems. Incremental predictive validity was assessed from 3, 5 and 7 minutes observation to attachment outcomes (Strange Situation; 14 months) and infant mental health (BITSEA; 14 and 30 months). Results: Excellent inter-rater reliability was evident at code and subscale level for each tool and observation period. Stability of withinrater agreement was optimal after 5 minutes observation. ROC analysis confirmed predictive (discriminant) validity (AUCs > .70) to top decile age 2 mental health outcomes for PIIOS total score and a brief 3-item composite from NICHD-SECCYD (sensitivity, intrusiveness, positive regard; NICHD-3), but not to attachment outcomes. Logistic regression showed dyads rated at-risk for externalizing problems using NICHD-3 were also at significantly higher risk for insecurity at 14 months (OR=2.7, p=.004). Conclusion: PIIOS total and NICHD-3 ratings from 5 minutes observation are both reliable and valid tools for use in clinical practice. Findings suggest NICHD-3 may have greater utility due to its comparative brevity to train and code, with suitability for use over a broader developmental time frame (3-24 months).